Relationship of screen time with anxiety, depression, and sleep quality among adolescents: a cross-sectional study - Mohd Saat, Nur Zakiah; Hanawi, Siti Aishah; Hanafiah, Hazlenah; Ahmad, Mahadir; Farah, Nor M. F.; Abdul Rahman, Nur Ain Atikah (Frontiers in Public Health, 2024)
IntroductionIn the current digital age, people’s use of electronic devices has significantly increased screen time, which may have an impact on different aspects of their lives. Adolescents today are exposed to excessive screen time, which may affect their sleep and contribute to anxiety and depression. The purpose of this study is to examine the relationship between screen time with sleep quality, anxiety and depression, among adolescents in Klang Valley, Malaysia.MethodsThis study is a cross-sectional study information was gathered from among 353 secondary school students in the Klang Valley using a questionnaire. The instrument that was used in this study was Pittsburgh Sleep Quality Index (PSQI) Malay version, screen-based media usage (SCREENS-Q) and Hopkins Symptom Check List-25 (HSCL-25) Malay version. The sampling method was stratified and convenience sampling method. The analysis study used the Smart Partial least squares (PLS) method to analyze the data.ResultsUsing the Smart PLS technique, we examined the relationship between these variables and identified revealed that screen time has a direct, positive, and significant impact on anxiety level (Mean = 0.134, β = 0.123, p < 0.01) and depression levels (Mean = 0.202, β = 0.194, p < 0.01). Moreover, screen time has a low effect on sleep quality (Mean = 0.128, β = 0.117, p < 0.05). However, the mediating factor, sleep quality, was not significant in the indirect effect of screen time with anxiety (Mean = 0.047, β = 0.040, p  > 0.05) and depression (Mean = 0.044, β = 0.043, p  < 0.05).DiscussionThis study highlights the importance of understanding the association between screen use, sleep quality, anxiety and depression. Notably, excessive screen time appears to be associated with poorer sleep quality, ultimately increasing anxiety and depression. Understanding the effects of excessive screen time on sleep and well-being may have a substantial impact on public health policies and interventions. Enacting policies that promote better screen habits and sleep hygiene could improve people’s overall quality of life and well-being in the digital age. However, more longitudinal research is needed to confirm the causality of these relationships and investigate potential intervention strategies.